Does extreme weather affect the resilience of agricultural economies? Analysis based on agricultural insurance - Zeng, Xiaoyan; Lu, Huiling; Qi, Huaqing; Ji, Long (Frontiers in Environmental Science, 2025)
IntroductionAgainst the backdrop of global warming and the frequent occurrence of extreme weather events, effectively bringing into play the effectiveness of agricultural insurance in supporting agriculture and enhancing the resilience of the agricultural economy is of universal significance for countries around the world. This study aims to explore the impact of extreme weather on the resilience of the agricultural economy, as well as whether agricultural insurance plays a role in the relationship between the two.MethodsBased on the panel data of 31 provinces (autonomous regions and municipalities directly under the Central Government) in China from 2011 to 2022, this paper selects 15 indicators from three dimensions, namely the pressure layer, the state layer, and the response layer, and measures the resilience of the agricultural economy by using the entropy method. Furthermore, through the fixed effects model and the moderating effects model, this paper empirically analyzes the impacts of extreme weather changes such as extreme high temperatures, extreme low temperatures, and extreme precipitation on the resilience of the agricultural economy, and examines the moderating role of agricultural insurance in this context. Finally, this paper explores whether the impacts of extreme weather on the agricultural economy in different regions are consistent, and the effectiveness of the role of agricultural insurance in different regions.ResultsThe study has revealed that extreme weather changes, predominantly characterized by extreme high temperatures, are detrimental to the enhancement of agricultural economic resilience. Conversely, agricultural insurance can effectively alleviate the negative impacts of extreme weather on the resilience of the agricultural economy. Meanwhile, the results of the heterogeneity test further validate the adverse effects of extreme weather on agricultural economic resilience and the negative moderating role of agricultural insurance therein. Overall, the adverse impacts of extreme weather are more pronounced in the central and eastern regions compared to the western region. Similarly, the moderating effects of agricultural insurance are more evident in the eastern and central regions than in the western region.DiscussionBased on the heterogeneity analysis, this study explores the reasons for the inconsistent impacts of extreme weather and agricultural insurance in different regions. By comparing the agricultural insurance systems of China with those of other countries, and further from an international perspective, a policy framework is constructed, which takes promoting the high-quality development of agricultural insurance and enhancing the resilience of the agricultural economy as its core. Based on this framework, this paper puts forward some suggestions that may help mitigate the adverse impacts of extreme weather changes on agricultural production and further steadily strengthen the resilience of the agricultural economy.